The effect of the COVID-19 pandemic lockdown measures on plastic, reconstructive and hand surgery emergency presentations – A comparative retrospective study in a regional referral center in Germany. (October 2022) - Obed, Doha; Salim, Mustafa; Ammo, Tekoshin; Gildt, Maria M.; Krezdorn, Nicco; Vogt, Peter M.; Dastagir, Khaled
Abstract: Background: The global COVID-19 pandemic has led to social constraints and changes in injury patterns during the government-imposed restrictions. The aim of this study was to evaluate the effects of the lockdown period on the pattern of emergency presentations in a plastic, hand and reconstructive surgery department in a German referral center. Methods: A retrospective cohort study was conducted comparing patients presenting during the enforced lockdown period in 2020 and the same pre-pandemic period during the previous year 2019. All emergency presentations in the emergency unit requiring treatment by plastic, hand and reconstructive surgery were included. Patient demographics, reason for presentation, need for hospital admission, body region affected, location of injury and/or occurrence of first clinical symptoms and injuries of anatomical structures were considered. Results: Demographics were comparable among both groups. A 42.7% reduction in emergency cases was observed during the lockdown period. A significant elevation of domestic injuries and symptoms in the pandemic group (51.54% vs. 66.15%, p = 0.007) was registered. Concurrently, a decrease in recreational injuries (27.31% vs. 15.38%, p = 0.009) and workplace injuries (10.57% vs. 7.69%, p = 0.37) was noted. Hospital admission rates and length of stay were comparable. Similarly, no statistically significant differences could be detected regarding injuries of functional anatomical structures. The same holds true for crush injuries, animal bites, fall injuries, finger amputations, disc saw injuries, and distortion injuries. Fractures of the phalanges, the metacarpus/carpus and the forearm exhibited an increase. Conclusions: In spite of decreasing total emergency caseloads, there was an unchanged need for plastic, hand and reconstructive in-patient surgery and care during the lockdown period. Resource allocation has to be considered in future pandemic waves. Prevention strategies are warranted and should focus on finding measures to counteract domestic injuries. Highlights: The COVID-19 lockdown caused a shift in surgical emergency case presentations. Increasing domestic and decreasing recreational and work injuries were noted. Middle-aged females were at high risk to sustain injuries during lockdown. Hand injuries showed consistent severity and hospital admission rates. Resource allocation remains crucial in future pandemic waves.